GENERATE JADWAL PERKULIAHAN - Asep Saepulloh; Agus Ramdhani Nugraha (JUTEKIN (Jurnal Teknik Informatika), 2014)
As we know that the development of science and technology is increasing, one of which is the development of computer technology perkembangnya very rapidly, because the computer is a means to obtain optimal results.In the beginning of the school year biasany often encounter problems when creating a schedule or timetable pelajarana in school lectures at the college. Given the importance of these two, the authors try to do research on the scheduling system in the College of Management and Computer DCI Tasikmalaya., The authors analyze and design systems to process the data subject, the data lecturer room data to generate schedules rapidly. In addition to scheduling can be done quickly, with the system we can get the information and results as a report that has not been done in the previous system.Administration play an important role, especially in making the course schedule or when operating the system Generate SCHEDULE PERKULIHAN. And the system is expected to be made to overcome the obstacles that arise well before the schedule is made and after the schedule is finished.As the results obtained from these studies, the authors propose the design of data processing student information system, which produce information and reports as expected  Keyword : Generate , Plants, Lecture Schedule